2012
DOI: 10.1016/j.jsbmb.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cholesterol, vitamin D3 and 20-hydroxyvitamin D3 incorporated into phospholipid vesicles by human CYP27A1

Abstract: CYP27A1 is a mitochondrial cytochrome P450 which can hydroxylate vitamin D3 and cholesterol at carbons 25 and 26, respectively. The product of vitamin D3 metabolism, 25-hydroxyvitamin D3, is the precursor to the biologically active hormone, 1α,25-dihydroxyvitamin D3. CYP27A1 is attached to the inner mitochondrial membrane and substrates appear to reach the active site through the membrane phase. We have therefore examined the ability of bacterially expressed and purified CYP27A1 to metabolize substrates incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 52 publications
(70 reference statements)
5
63
1
Order By: Relevance
“…Since liver mitochondria contain at least one P450, CYP27A1, that can metabolize 20(OH)D3 (19), we tested the level of contamination of the microsomal fraction with mitochondria using cytochrome c oxidase as a marker. The mitochondrial fraction exhibited a cytochrome oxidase activity of 6.75 ± 0.6 nmol/min/mg protein (data are mean ± SD for triplicate determinations), while the microsomal fraction exhibited an activity of 0.37 ± 0.05 nmol/min/mg protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since liver mitochondria contain at least one P450, CYP27A1, that can metabolize 20(OH)D3 (19), we tested the level of contamination of the microsomal fraction with mitochondria using cytochrome c oxidase as a marker. The mitochondrial fraction exhibited a cytochrome oxidase activity of 6.75 ± 0.6 nmol/min/mg protein (data are mean ± SD for triplicate determinations), while the microsomal fraction exhibited an activity of 0.37 ± 0.05 nmol/min/mg protein.…”
Section: Resultsmentioning
confidence: 99%
“…22-Hydroxyvitamin D3 [22(OH)D3], 17,20(OH) 2 D3, 20,22(OH) 2 D3 and 20,23(OH) 2 D3 were also produced from vitamin D3 using bovine CYP11A1 (16). 20,24-dihydroxyvitamin D3 [20,24(OH) 2 D3] and 20,25(OH) 2 D3 were produced by the action of rat Cyp24a1 on 20(OH)D3 (18) while 20,26-dihydroxyvitamin D3 [20,26(OH) 2 D3] was made from 20(OH)D3 using human CYP27A1 (19). The structures of these metabolites have previously been determined by NMR (5,16,18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that 20(OH)D3 can be hydroxylated by two vitamin D-metabolizing enzymes, human CYP27A1 (Tieu et al, 2012a) and rat CYP24A1 (Tieu et al, 2012b). The main products of CYP24A1 action on 20(OH)D3 are 20,24(OH) 2 D3 and 20,25(OH) 2 D3, and for CYP27A1 are 20,25(OH) 2 D3 and 20,26(OH) 2 D3.…”
Section: Discussionmentioning
confidence: 99%